Effection of Chlorine-Doped TiO2 Photocatalysts for Photocatalytic Activity - Liu, Xinlin; Lv, Peng; Yao, Guanxin; Yan, Yan; Huo, Pengwei; Yan, Yongsheng (Asian Journal of Chemistry, 2013)
The photocatalyst Cl-TiO2 is prepared using the sol-gel method. The light absorption of the Cl-TiO2 red shifts and extended the absorption spectrum (l > 400 nm). The photocatalyst of Cl-TiO2 is characterized by the UV-visible diffuse reflection spectroscopy, scanning electron microscopy, X-ray powder diffraction and X-ray photoelectron spectroscopy. The photocatalytic activity of as-prepared samples was evaluated by degradation of ciprofloxacin under visible light irradiation, with degradation rate of 50.69 % in 1 h. The results show that the photocatalytic activity of the Cl-TiO2 photocatalyst is lower than that of pure TiO2. Our work highlights the simple way to modify TiO2 photocatalyst for practical use.